2011
DOI: 10.1007/s12177-012-9085-y
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear GAPDH: changing the fate of Müller cells in diabetes

Abstract: Müller cells, the primary glial cells are a crucial component of the retinal tissue performing a wide range of functions including maintaining the blood-retinal barrier. Several studies suggest that diabetes leads to Müller cell dysfunction and loss. The pathophysiology of hyperglycemiainduced cellular injury of Müller cells remains only poorly understood. Recently, the concept that translocation of the predominantly cytosolic glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) to the nucleus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
8
1
Order By: Relevance
“…In some studies, no cell death was observed after 72 h [ 30 ] or after 5 days in HG [ 90 ], while others detected Müller cell apoptosis after 72 h in the same conditions, possibly related to AKT inhibition [ 33 ]. In favor of an apoptotic mechanism is the observation that in rMC-1 and in cultured human primary Müller cells incubated in HG conditions, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) translocates to the nucleus [ 91 ]. A similar nuclear accumulation of GAPDH in Müller cells was observed in retinal sections from diabetic rats at 4 months of diabetes [ 91 ].…”
Section: Müller Glia Involvement In Drmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, no cell death was observed after 72 h [ 30 ] or after 5 days in HG [ 90 ], while others detected Müller cell apoptosis after 72 h in the same conditions, possibly related to AKT inhibition [ 33 ]. In favor of an apoptotic mechanism is the observation that in rMC-1 and in cultured human primary Müller cells incubated in HG conditions, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) translocates to the nucleus [ 91 ]. A similar nuclear accumulation of GAPDH in Müller cells was observed in retinal sections from diabetic rats at 4 months of diabetes [ 91 ].…”
Section: Müller Glia Involvement In Drmentioning
confidence: 99%
“…In favor of an apoptotic mechanism is the observation that in rMC-1 and in cultured human primary Müller cells incubated in HG conditions, glyceraldehyde-3-phosphate dehydrogenase (GAPDH) translocates to the nucleus [ 91 ]. A similar nuclear accumulation of GAPDH in Müller cells was observed in retinal sections from diabetic rats at 4 months of diabetes [ 91 ].…”
Section: Müller Glia Involvement In Drmentioning
confidence: 99%
“…Therefore, it is considered that the microtubule encoding protein of human islet tissue TUBA1C might be related with the insulin secretion [25]. Another gene GAPDH , connected with a differentially methyalted gene, although the DNA methylation level of this gene was not aberrant, researches have shown that, this gene could change the etinal Müller cells fate in diabetes[26], and Müiler cells are the most important retinal glial cells of vertebrate[27]. It is shown that H3K4me3 was negatively correlated with DNA methylation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, hyperglycemia stimulates GAPDH accumulation in the nucleus of retinal Müller cells, in association with the apoptosis of these cells. [ 47 , 50 ]. It is possible that Müller cell death could also affect RGCs, accentuating the deleterious effect of glucose on RGCs.…”
Section: Discussionmentioning
confidence: 99%